Towards automation of fibre to the home planning with consideration on OPTIC access network model. (1st January 2021) - Naeem, Abid; Ahmed, Sheeraz; Khan, Muhammad Yousaf Ali; Safwan, Nadeem; Khan, Zahoor Ali
Owing to the rapid technological evolution, tough competition and budget limitation, the service providers are struggling to provide a cost-effective solution to minimise their operational cost with extraordinary customer satisfaction. One of the factors that increase the cost of overall Fibre To The Home (FTTH) network is the unplanned deployment resulting in utilisation of extra components and resources. Therefore, it is imperative to determine a suitable technique, which helps to reduce planning process, required time and deployment cost through optimisation. With the intention to meet the increasing demand of future higher bandwidth applications, the fibre-based access is considered best resolution to deliver triple play services (voice, data, video). It is therefore preferred with great need to migrate from traditional copper-based network to fibre-based access. Automation-based planning is one of the possible ways to automate the network design at probable lowest cost. In this research, a technique for migration from copper to fibre access network with a climbable and optimised Passive Optic Network (PON-FTTx) infrastructure is proposed identifying the need for new technology in developing countries.